Platform for Distributed 3D Gaming - A. Jurgelionis; P. Fechteler; P. Eisert; F. Bellotti; H. David; J. P. Laulajainen; R. Carmichael; V. Poulopoulos; A. Laikari; P. Perälä; A. De Gloria; C. Bouras (International Journal of Computer Games Technology)
Video games are typically executed on Windows platforms with DirectX API and require high performance CPUs and graphics hardware. For pervasive gaming in various environments like at home, hotels, or internet cafes, it is beneficial to run games also on mobile devices and modest performance CE devices avoiding the necessity of placing a noisy workstation in the living room or costly computers/consoles in each room of a hotel. This paper presents a new cross-platform approach for distributed 3D gaming in wired/wireless local networks. We introduce the novel system architecture and protocols used to transfer the game graphics data across the network to end devices. Simultaneous execution of video games on a central server and a novel streaming approach of the 3D graphics output to multiple end devices enable the access of games on low cost set top boxes and handheld devices that natively lack the power of executing a game with high-quality graphical output.